Repetitive acceptance sampling plan for type-ii generalized half logistic distribution based on truncated life test - Gadde Srinivasa Rao; Sd. Jilani; A. Vasudeva Rao (Songklanakarin Journal of Science and Technology (SJST), 2021)
In this article, we present a new repetitive acceptance sampling plan for attributes based on considering the Type-II generalized half-logisticl distribution (GHLD) with known shape parameters. The plan parameters such as sample size and acceptance number are formulated by considering the median lifetime of test as a quality parameter. The objective function to be mimimized is the average sample number(ASN), whereas the constraints are related to the lot acceptance probalilities at the acceptable and limiting quality levels. The authors compare the average sample number (ASN) of the proposed repetative acceptance sampling plan and the ordinary single sampling plan. Tables are constructed for various values of shape parameter. The results are demonstrated with the help of real- life data.